The Significance of St. John’s Day in the Socio-Cultural Space of the Lithuanian-Latvian Borderland - Noreikaitė, Aukse (Acta humanitarica academiae Saulensis, 2025)
The object of the article is St. John’s Day in the socio-cultural space of the Lithuanian-Latvian borderland. The aim is to find out what significance the St. John’s Day had in different border areas. Empirical material collected by the author in several stages (in 2008–2019) as well as the press were used to reveal the topic. The methods applied in this research were quantitative content analysis, case analysis, interpretive, and comparative methods. The theoretical approaches of anthropologists and sociologists talking about the construction of identity were relevant for the analysis of the topic.St. John’s Day is an important cultural attribute of the Lithuanian-Latvian borderland, reflecting the ethnic and social processes that took place and are still taking place here. In the socio-cultural space of the borderland, St. John’s Day performed functions related to the formation of both Latvian and Lithuanian ethnic identity. In some places, this festival acted as a very clear ethnic boundary marker, which also had a physical form – a festive attribute of fire, i.e. Joninės expressed the identity of the Latvian ethnic group. In other places, Joninės was an important sign of ethnic identity for both Lithuanians and Latvians, but ethnic difference was expressed through the national language, i.e. during the festival it was important not only to speak the relevant language, but also to use the cultural attributes related to it – songs, dances or games. It has also been observed that St. John’s Day celebration served a social capital function, i.e. it was a tool that helped to rise in the social hierarchy. In other words, it is typical for actors in the socio-cultural space of the Lithuanian-Latvian boderland to strive to be culturally equal to the Latvian ethnic group, which had a significant role in this border region, and in some areas even a higher status. Finally, this festival played an important role of ethnic tolerance –- it united the community of a particular village or town, and at the same time helped to form a distinctive and multi-layered local identity of the borderland resident.
Keywords: St. John's Day; ethnic identity; ethnic markers; Lithuanian-Latvian borderland